The Impact of Divorce on Children from a Sociology of Law Perspective: A Case Study in Tondong Tallasa District - Sikra; Basri, Rusdaya (MAQASIDI: Jurnal Syariah dan Hukum, 2025)
This study examines the impact of divorce on children from a sociology of law perspective in Tondong Tallasa District. The objectives of this research are to identify the effects of divorce on children and to analyze the factors contributing to divorce in Tondong Tallasa District. The research employs a descriptive qualitative method, which is a problem-solving procedure that investigates phenomena by describing and portraying the conditions of the research subjects or objects as they currently exist, based on observable facts. Data were collected through observation, interviews, and documentation. The collected data were analyzed by reviewing and synthesizing the findings to produce concise thematic summaries. The results of the study indicate that the causes of divorce in Tondong Tallasa District vary, including: (1) domestic violence, (2) infidelity, (3) economic factors, and (4) parental interference. Furthermore, the impact of divorce on children is generally similar, namely that children tend to become less open with others and experience feelings of shame in relation to their peers.